Wind Energy Expansion and Wildlife Conservation: A Critical Review of Challenges and Solutions - Ojong Felix Enow,; Ebimor Yinka Gbabo,; Andrew Tochukwu Ofoedu,; Possible Emeka Chima,; Oluwapelumi Joseph Adebowale,; Oluwapelumi Joseph Adebowale, (International Journal of Scientific Research in Science and Technology, 2025)
The global push towards renewable energy, particularly the rapid expansion of wind power, has raised concerns about its potential impact on wildlife. This critical review delves into the intricate relationship between wind energy expansion and wildlife conservation, aiming to identify the challenges posed and explore potential solutions for harmonizing these seemingly conflicting objectives. The expansion of wind energy infrastructure presents a multifaceted challenge for wildlife conservation. One of the primary concerns is the potential threat posed by wind turbines to avian populations, as birds and bats can collide with the rotating blades. This paper critically examines the available research on bird and bat fatalities, considering species-specific vulnerabilities and regional variations. Additionally, the displacement of wildlife due to habitat fragmentation caused by wind farm development is analyzed, emphasizing the importance of preserving ecosystems and mitigating adverse impacts on biodiversity. Solutions to these challenges are explored through a comprehensive lens, addressing both technological and policy-driven interventions. Innovations such as radar-based monitoring systems, blade design modifications, and strategic placement of wind turbines are discussed as means to minimize the risk to wildlife. Furthermore, the importance of robust environmental impact assessments and comprehensive planning is highlighted to ensure sustainable wind energy development. The review also underscores the significance of collaborative efforts between the renewable energy industry, conservation organizations, and policymakers. Balancing the imperatives of clean energy and wildlife preservation requires a holistic approach that considers ecological sensitivity alongside energy production goals. In conclusion, this critical review provides a nuanced analysis of the challenges associated with the expansion of wind energy and its implications for wildlife conservation. By synthesizing current knowledge and proposing practical solutions, it contributes to the ongoing discourse surrounding the imperative to strike a balance between renewable energy goals and the preservation of global biodiversity.
Keywords: Wind Energy; Wildlife; Conservation; Renewable Energy; Review